1999
DOI: 10.1080/00224549909598252
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Social Interaction in Societies of the Asia–Pacific Region

Abstract: The authors developed an 18-item Social Interaction Inventory that yielded a factorial structure based on the 3 domains of social interaction: interpersonal, personal, and extrapersonal. They administered the inventory to samples from 15 countries of the Asia-Pacific region (N = 146). The participants in the different cultural groups preferred to interact more within the interpersonal (in-group) domain as compared with the personal (individual) and extrapersonal (out-group) domains. The findings reflect a coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…In addition although physical risk factors may be similar in many populations worldwide, associated psychosocial risk factors will differ from one populations to another, thus in this context the South-Asian population could be different from counterparts in rest of the world. Indeed studies from the region have demonstrated that they demonstrate a collective pattern, rather than an individualistic pattern, of social interaction [21]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition although physical risk factors may be similar in many populations worldwide, associated psychosocial risk factors will differ from one populations to another, thus in this context the South-Asian population could be different from counterparts in rest of the world. Indeed studies from the region have demonstrated that they demonstrate a collective pattern, rather than an individualistic pattern, of social interaction [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Inferences may also be drawn regarding Asian Indian students' preference for mentoring unemployed people with disabilities rather than those who were employed. Because of their strong collectivistic identity, Asian Indian students may feel a commitment and duty toward the community at large, extending beyond family and friends (Dadkah et al, 1999). Their preference for mentoring unemployed people with disabilities may indicate that students perceived them as needing more help in getting integrated into the community, as compared to employed individuals with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have suggested (Groce, 1990;Triandis, 1996) that societies develop patterns of coping with a disability incumbent on their cultural beliefs, shared values, social cognitive processes, and affective meanings (Dadkah, Harizuka, & Mandal, 1999). An understanding of Asian Indians' perceptions of people with disabilities, their causal attributions for onset of disabilities, and their help-seeking behavior would allow counselors and other professionals to provide culturally competent and appropriate services.…”
Section: An Asian Indian View Of Disabilitymentioning
confidence: 99%
“…As such, Vanuatu is highly representative of child-rearing environments in much of the world. Socialization in Vanuatu is based on fostering collective and cooperative values with a strong emphasis on social conformity (Dadkhah, Harizuka, & Mandal, 1999; Little, Carver, & Legare, 2016; Peck & Gregory, 2005; Strachan, Samuel, & Takaro, 2007; Walker, 2013). In addition, previous work has indicated that Ni-Vanuatu children imitate behavior with higher levels of fidelity than U.S. children in experimental assessments of social learning, potentially due to differences in cultural expectations for conformity (Clegg & Legare, 2016a).…”
mentioning
confidence: 99%